Engagement and Emotional Intelligence in Students of a Private University in the City of Arequipa - Arias-Chávez, Dennis (2020)
The objective of this study was to determine the relationship between engagement and emotional intelligence in male and female students of a private university in Arequipa. For this, a sample of 246 students of the first semester (117 women and 129 men) was taken. Two instruments were applied: the EQI Bar-On (Emotional Quotient Inventory) test adapted by Ugarriza and Pajares and the Utrecht Work Engagement Scale (UWES-9) adapted by Schaufeli and Bakker. The design is of a non-experimental type of relationallevel. The results indicate that the average emotional intelligence obtained in the students was 77.04, out of 120 possible points. Regarding the engagement variable, an average of 51.09 was reached, with a maximum of 68 points. Regarding the correlationsof the engagement variable with the components of the emotional intelligence variable and with the same emotional intelligence variable stratified by sexes, it is observed that in women there is a relationship between engagment and interpersonal, intrapersonal, adaptability, impression components. and with the variable emotional intelligence, while in men the correlations range from .383 to .202.